2017
DOI: 10.3390/molecules22020299
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Phytochemistry, Pharmacology, and Pharmacokinetics of Amentoflavone, a Naturally-Occurring Biflavonoid

Abstract: Amentoflavone (C30H18O10) is a well-known biflavonoid occurring in many natural plants. This polyphenolic compound has been discovered to have some important bioactivities, including anti-inflammation, anti-oxidation, anti-diabetes, and anti-senescence effects on many important reactions in the cardiovascular and central nervous system, etc. Over 120 plants have been found to contain this bioactive component, such as Selaginellaceae, Cupressaceae, Euphorbiaceae, Podocarpaceae, and Calophyllaceae plant families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 138 publications
4
117
0
2
Order By: Relevance
“…Earlier report suggest diverse pharmacological activities of Amentoflavone. 16 The therapeutic effect on cardiovascular and central nervous system was also reported in earlier studies. [17][18][19] Alphasynuclein is the characteristic property of Parkinson's disease; hence, it has an important application in the clinical diagnosis and therapeutics of Parkinson's disease.…”
Section: Discussionsupporting
confidence: 57%
“…Earlier report suggest diverse pharmacological activities of Amentoflavone. 16 The therapeutic effect on cardiovascular and central nervous system was also reported in earlier studies. [17][18][19] Alphasynuclein is the characteristic property of Parkinson's disease; hence, it has an important application in the clinical diagnosis and therapeutics of Parkinson's disease.…”
Section: Discussionsupporting
confidence: 57%
“…In recent years, iridoids have been proven to have a wide range of biological activities, and their pharmacokinetic characteristics have also been widely studied [112]. The different structures of parent nuclei of iridoids result in different metabolic pathways, mainly through the hydrolysis of β-glucosidase, glucose-aldeacidification, isomerization, and other metabolic processes throughout the body [8].…”
Section: Pharmacokinetic Of Iridoidsmentioning
confidence: 99%
“…Amentoflavone ( Figure 1A) is a common biflavonoid isolated from a variety of traditional Chinese medicines, such as Selaginella tamariscina or Ginkgo biloba (Yu et al, 2017). Previous studies have indicated that amentoflavone has multiple pharmacological effects, including anti-inflammatory (Zhang et al, 2015), antioxidant (Saroni Arwa et al, 2015), antivirus (Li et al, 2019), and antitumor activities (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%